Another look on safety climate and safety behavior: deepening the cognitive and social mediator mechanisms - Fugas, C. S. (2014)
In this study, safety climate literature and the theory of planned behavior were combined to explore the cognitive and social mechanisms that mediate the relationship between organizational safety climate and compliance and proactive safety behaviors. The sample consisted of 356 workers from a transportation organization. Using a multiple mediation design, the results revealed that proactive and compliance safety behaviors are explained by different patterns of combinations of individual and situational factors related to safety. On the one hand, the relationship between organizational safety climate and proactive safety behaviors was mediated by coworkers' descriptive norms and attitudes toward safety. On the other hand, supervisors' injunctive safety norms and perceived behavioral control were the mediator variables between organizational safety climate and compliance safety behaviors. Theoretical and practical implications of the findings are discussed.